Konsep Pendidikan Anak Dalam Perspektif Munif Chatib - Rofik Andi Hidayah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Abstract: This study aimed to find the concept of children'a ducation in the perpective of Munif Chatib. There are several things that need to be considered by the school in the implementation of the concept of children's education. First, the input activity, which is marked by the admission of new students in a school. The school is focused on the quality of student input. The quality of the learning process depends on the quality of teachers. The teachers who are able to guarantee all students will be guided towards better change, regates all the potential inherent in student. Second, the activities of the procces that studenta diverse learning styles in the information transfer procces or a learning proccess that aims to mastery learning outcome indicators. There are four steps that must be implemented by school, namely; (1) Brain; (2) teaching strategy; (3) Product; and (4) Benefit. Third, the output (result) based on the cognitive students. Keywords: education, children, Munif Chatib.